For a Left Populism - Demir, Gokhan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
Mouffe's For a Left Populism suggests a leftist populist strategy to intervene in the post-2008 crisis of the neoliberal hegemonic formation. Left populism is a discursive strategy that seeks to draw a political boundary between the people and the oligarchy and against inequalities produced by neoliberal capitalism. Its intention is to come to power by building a people, constructing a collective will, and, accordingly, deepening democracy. The book attempts to restore the harmony between liberalism and democracy that neoliberalism has annihilated. Thus, it proposes an alternative to the neoliberal hegemonic formation. Mouffe's search for an alternative starting point for a socialist strategy ends with left populism versus postdemocracy.
Keywords: Hegemony; Left Populism; Neoliberalism; Postdemocracy; Radical Democracy; Government & Law